DISTANCE EDUCATION AND ITS TYPES, BASICS OF DISTANCE EDUCATION ORGANIZATION - Xolmurodov Shuxrat Okboyevich; Aynazarov Bakhtiyor Abdimuminovich (Web of Journals Publishing, 2024)
Distance education and its types, the impact of education on today, distance education technologies were discussed.
Keywords: Distance learning, Teacher, learner and communication, Distance learning, LMS, communication tools, gamification tools, online platforms, save money, save time, high probability of distraction, disconnection, Another important disadvantage.